MORPHOLOGICAL CHANGES OF THE KIDNEY OF INFANTS WHO DIE FROM ASPIRATION SYNDROME (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Conclusion. Aspiration syndrome in the early postpartum and late neonatal periods remains one of the relevant research topics in neonatology, with still less emphasis on postpartum aspiration in newborns and infants, despite its clinical significance.The purpose of the work . Observation of specific morphological changes in the development of the kidney of infants who died from Aspiration Syndrome in the early and late neonatal period after childbirth in postnatal ontogenesis.Object and subject of research. At the Republican Center for pathological anatomy, a total of 48 patients in the postnatal neonatal period 2020-2023 received kidney tissue material from infants and infants who died early (0-7 days) of the neonatal period.Results obtained. Infants with Aspiration Syndrome during the period of up to 7 days due to renal hypoxia, epithelial cell necrosis is usually arang-palpable and is detected with difficulty of the basal membranes. The distal part of the ducts and the presence of protein cylinders in the collecting tubes are evidence of Aspiration Syndrome. We have observed that cells that have undergone necrosis and migrate pass into the lower sections of the ducts and form cylinders. It will be possible to predict the accumulation of lymphocytes, macrophages around the affected membrane.Conclusion: microscopic tests of kidney tissue show that we study morphological changes in kidney tissue isolated in autopsies of infants diagnosed with Aspiration Syndrome in the neonatal period. Necrotic change in the kidney, which begins at a time when blood circulation is impaired, that is, when oxygen does not reach well, is referred to as ischemic duct necrosis. In this case, we will be able to see that the proximal part of the ducts and the descending part of the genle bladder are damaged. The onset of acute kidney failure is indicated by necrosis of the ducts.